Investigating SATS-36 for a Matriculation Sample - Krishnan, Saras; Idris, Noraini (Institute of Advanced Engineering and Science, 2015)
Students’ attitudes towards statistics have been more often negative due to many factors such as initial perception of the subject, low ability in mathematics and lack of motivation to study statistics. Studies involving SATS-36 included investigation of the different factors in relation to students’ attitude towards statistics. Other studies have investigated the structure of SATS-36 and the relationship between the different components of SATS-36. The research investigated the reliability and validity of SATS-36 for a sample of matriculation students. Results showed that while reliability and validity is maintained for the instrument, it is not the case for the sample of respondents.